2019
DOI: 10.1001/jamanetworkopen.2019.14031
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Oral Human Papillomavirus Infection Among Sexually Active Female Adolescents Receiving the Quadrivalent Vaccine

Abstract: This cohort study assesses associations between sexual activity, the oral presence of human papillomavirus (HPV), and HPV vaccination among sexually active female adolescents vaccinated against 4 HPV types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…Quadrivalent Gardasil shows excellent efficacy against cervical HPV infection, cervical cancer precursor lesions, and genital warts caused by the HPV types covered by Gardasil [ 9 , 11 ]. In addition, studies demonstrated that Gardasil significantly decreases HPV infections in the anus, vulva, and penis, as well as in the oral cavity related to HPV vaccine types [ 12 , 13 , 14 ]. Gardasil has a strong prevention rate (>90%, injection prior to HPV exposure) against CIN 2 or worse (CIN 2+), CIN 3+ and vulvar/vaginal intraepithelial neoplasia grade 2 or worse (VIN/VaIN 2+), caused by HPV 16 and 18 [ 6 , 41 ].…”
Section: Hpv Vaccine Efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…Quadrivalent Gardasil shows excellent efficacy against cervical HPV infection, cervical cancer precursor lesions, and genital warts caused by the HPV types covered by Gardasil [ 9 , 11 ]. In addition, studies demonstrated that Gardasil significantly decreases HPV infections in the anus, vulva, and penis, as well as in the oral cavity related to HPV vaccine types [ 12 , 13 , 14 ]. Gardasil has a strong prevention rate (>90%, injection prior to HPV exposure) against CIN 2 or worse (CIN 2+), CIN 3+ and vulvar/vaginal intraepithelial neoplasia grade 2 or worse (VIN/VaIN 2+), caused by HPV 16 and 18 [ 6 , 41 ].…”
Section: Hpv Vaccine Efficacymentioning
confidence: 99%
“…The most common HPV types found in anal carcinoma are HPV16, 18, 31, 33, and 45, which are all covered by the current Gardasil 9 vaccine [ 85 , 86 ]. Some studies have suggested that HPV vaccination could protect against the progression of oral cancers, as oral HPV infection can be effectively inhibited by HPV vaccines [ 10 , 12 , 13 ]. However, this issue has not been fully addressed owing to the lack of alignment between vaccine availability and the changes in cancer development over time [ 87 , 88 ].…”
Section: Male Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were abstracted from each study and a meta-analysis performed to calculate the prevalence of oral hr-HPV infection, the incidence of OPSCC, and the proportion of hr-HPV–related OPSCC among Indigenous and/or non-Indigenous populations. A random effects meta-analysis model was used to generate 3 pooled summary estimates and forest plots from 47 studies: 14 for oral hr-HPV infection in Indigenous/general population, 13,22-34 6 for OPSCC among Indigenous and non-Indigenous populations, 16,35-39 and 27 for hr-HPV–related OPSCC. 6,7,40-64 These were then combined into a single summary estimate to enable greater precision.…”
Section: Methodsmentioning
confidence: 99%